Analysis of Nanoparticles on Peristaltic Flow of Prandtl Fluid Model in an Endoscopy - Nadeem, S.; Sadaf, Hina; Adil Sadiq, M. (Current Nanoscience, 2014)
In this article, peristaltic flow of a Prandtl fluid model in an endoscope is analyzed in the presence of nanoparticles. Prandtl fluid model describe the shear thinning effects, another name for a shear thinning fluid is a pseudoplastic. This property is originated in certain complex solutions such as ketchup, fruit juice concentrates, shampoo, slurries, paint etc. The flow is modeled in both fixed and wave frame of reference. We have used homotopy perturbation method for the solutions of velocity profile, nanoparticles concentration and temperature profile. The results for velocity temperature, nanoparticles concentration, pressure rise, frictional forces, pressure gradient and stream lines are presented to interpret the behavior of various physical quantities of Prandtl fluid model along nanoparticles. The results for various wave forms are also presented and plotted.
Keywords: Endoscopy